Unusual case of Candida Krusei implicated in Ludwig's angina and deep neck necrotising infection. Issue 3 (May 2022) - Aljefri, Maha; Khalid, Farhan; Lal, Pankaj; Dodd, Martin
Abstract: Ludwig's angina is a potentially life-threatening condition described as diffuse cellulitis of the neck involving bilateral submandibular and sublingual spaces, and manifests as swelling, trismus, dysphagia, drooling and dyspnoea. Odontogenic infections, mostly bacterial and related to a unilateral molar tooth are implicated in most of the cases. We present an unusual and rare case of deep neck necrotising infection involving bilateral lower third molars with Candida Krusei as a causative agent in a fit and healthy young male. This fungus is rarely disease-causing in humans and is resistant to commonly used antifungal medications. To the authors' knowledge, this organism has not been previously known to cause cervicofacial infections nor has it been reported to do so in the literature.